Hydroxyl and nitrate co-upgrading to oxime via anode-cathode cascade electrolyzer - Ouwen Peng; Qikun Hu; Mengtian Jin; Mengyao Su; Jia Liu; Bo Li; Shibo Xi; Chun Cheng; Kian Ping Loh (Nature Communications)
Abstract Oximes are crucial intermediates in the production of polymers and pharmaceuticals. Conventional synthesis methods, involving the hydrogenation of nitrogen oxides and nucleophilic addition of hydroxylamine to carbonyl compounds, are energy-intensive and hazardous. Here, we report an economical and sustainable electrosynthesis route to oximes using hydroxyl compounds and nitrate in an anode-cathode cascade electrolyzer. In this system, hydroxyl compounds are first dehydrogenated to ketones at a cobalt oxyhydroxide anode, followed by the subsequent co-reduction of ketones with nitrate at a Cu-substituted Fe3C cathode to form oximes. The cascade electrolyzer exhibits robust performance over 72 h at 2.8 V, achieving a high pyruvatoxime yield of 2.61 mmol cm–2 h–1 with a Faradaic efficiency of 101%. This versatile method accommodates diverse feedstocks, enabling the production of various relevant commodities. Process modeling and techno-economic analysis confirm the viability and cost-effectiveness of this innovative approach, offering a more sustainable pathway to essential chemical intermediates.